Reality or mirage? representations of African Union agenda in Kenyan and Zimbabwean newspapers. - Orina, Gladys K.; Mapuwei, Nyasha (Midlands State University, 2017)
The journey to the realisation of the African unity has been marked by many challenges that are political, social, cultural, commercial and historical. Arguably, the African dream is still alive and the effective communication of the African dream could be one of the pillars of its realisation. The past decade however, has seen a consistent paling of the hope as media discourse in the form of editorials and commentaries reflect that the dream is an uphill task. This paper critically examines the impact of media coverage of the African Union. Specifically, this paper assesses how, why and to what extent media representations of the subject of African unity in editorials and commentaries affected its implementation. The paper looks at some of the African media, mainly newspapers and news agencies portrayal of the African Union. Key research methods used in this study include archival research, textual analysis and content analysis. Based on the mass communication theories of gate-keeping, agenda setting, representation, media and political economy theories, this paper argues that the media casting and portrayal of the AU has a direct impact on the success or failure of its agenda. The paper found out that the overall underlying tone of newspaper editorials were dismissive and negative and contributed very little towards helping the AU achieve its objectives.